VACCINE INJURY - BURDEN OF PROOF OF THE DEFECT AND THE CAUSAL LINK IN THE LIGHT OF THE JUDGMENT IN THE CASE C-621/15 (EU and comparative law issues and challenges series (ECLIC), 2019)
In the European Union the liability of producers for harm caused by defective products manufactured or imported by them is regulated in Directive 85/374/EEC of 25 July 1985 on the liability for defective products. The purpose of Directive is to lay down a system of producer liability for damage caused by a defect in its product. Crucial is that it sets out a system of strict liability, so that the injured person does not have to show evidence of fault on the part of the producer. The injured person will have to prove the defect, the damage and the causal link between these. However, when it comes to the damage caused by vaccines, in case law the causal link has often been almost impossible to prove because in the scientific literature there are a number of opposing views on the risk of vaccination. Nevertheless, to the facilitation of the victims burden of proof could contribute the judgement of the Court of the European Union according to which a national court may consider that vaccination has led to the disease or damage even when there is no proof based on medical research. But, if there are other serious, specific and consistent evidence, such as the temporal proximity between the vaccination and the occurrence of a disease, the lack of personal and familiar history of that disease, together with the existence of other reported cases of the disease that occurred after such vaccines being received. Still, the Court retains caution by opposing any presumptions and warns that such cases are extremely fact-specific and require careful case-by-case considerations. In this article the author discusses the aforementioned judgement about liability for vaccine injury and its implications in the European Union.